Comparative financial performance of Islamic banks under diverse legal and regulatory systems in Southeast Asia - Rahmadi, Rahmadi; Wemona Rahma, Dea; Fata, Muhammad Indra; Naufal, Faris (Journal of Islamic Economics Lariba, 2025)
IntroductionIslamic banking has become an integral component of financial systems in many Muslim-majority and non-Muslim countries, yet its performance varies considerably across jurisdictions. These variations are closely linked to differences in legal frameworks, regulatory regimes, and institutional arrangements governing Islamic finance. In Southeast Asia, Indonesia, Malaysia, and Singapore represent three distinct regulatory models—hybrid Shariah-based, fully institutionalized Shariah-based, and conventional legal systems accommodating Islamic banking. Understanding how these differing environments shape the financial performance of Islamic banks remains an important and underexplored issue in comparative Islamic finance research.ObjectivesThis study aims to analyze and compare the financial performance of Islamic banks operating in Indonesia, Malaysia, and Singapore within the context of their respective legal and regulatory environments. Specifically, it seeks to examine differences in profitability, operational efficiency, intermediation activity, and capital adequacy, while interpreting these differences through an institutional and legitimacy-based perspective.MethodThe study employs a quantitative, descriptive–comparative research design using secondary data drawn from audited annual reports of selected Islamic banks during the 2021–2023 period. Financial performance is measured using Return on Assets, Return on Equity, Financing-to-Deposit Ratio, Operating Expenses to Operating Income Ratio, and Capital Adequacy Ratio. The analysis is conducted through ratio-based comparison at both intra-country and inter-country levels to capture institutional and regulatory influences on performance outcomes.ResultsThe findings indicate that Indonesian Islamic banks demonstrate relatively high profitability, largely driven by niche strategies such as microfinance, but exhibit heterogeneous efficiency and conservative intermediation in some cases. Malaysian Islamic banks show stable profitability, strong intermediation, and balanced capital adequacy, reflecting regulatory coherence and mature Shariah governance. Islamic banking units in Singapore achieve superior operational efficiency and improving profitability despite operating within a conventional legal framework, supported by advanced technology and scale economies.ImplicationsThe results highlight that Islamic banking performance is strongly shaped by institutional context rather than by a single optimal regulatory model. Regulators and practitioners should therefore design adaptive frameworks that balance prudential oversight, efficiency, and growth, while remaining responsive to local market conditions.Originality/NoveltyThis study contributes to the literature by providing a tri-country comparative analysis that integrates institutional and legitimacy perspectives, offering new empirical insights into how Islamic banks perform under hybrid, fully Shariah-based, and conventional legal systems in Southeast Asia.